Dapatkah Bersyukur Dan Kontrol Diri Mencegah Criminal Thinking Narapidana Kasus Kekerasan Seksual ? - Imaduddin Hamzah; Putri Rahmawaty Herlambang (JURNAL PSIKOLOGI, 2021)
The purpose of this study is to examine the relationship between gratitude, self-control, and criminal thinking. The majority of gratitude studies mostly focus on their relationship with well-being, life satisfaction, and prosocial behavior in normal and psychological disorders. Studies on the relationship between gratitude and deviant behavior are still very limited. This study uses correlational analysis and mediation of the relationship of gratitude, self-control, and criminal thinking of prisoners in sexual violence cases. The measurement of eighty-five prisoners in Kediri Penitentiary using the gratitude scale, Grasmick et al. 's self-control scale, and the Psychological Inventory of Criminal Thinking Style (PICT). This study's results found a direct effect of gratitude with criminal thinking; however, self-control shows a weak role in the index effect as a mediator. This finding has implications for the importance of developing a rehabilitation program on the psychological aspects of being grateful for inmates in prisons.